Experimental and theoretical study of the use of multifunctional initiators in the high impact polystyrene bulk process. Issue 2 (21st April 2017) - Berkenwald, E.; Laganá, M. L.; Maffi, J.M.; Acuña, P.; Morales, G.; Estenoz, D.
Abstract : The performance of three multifunctional peroxide initiators in a bulk high impact polystyrene (HIPS) process was experimentally and theoretically investigated. For the experimental work, a series of batch reactions was carried out, comprising the main stages of an industrial HIPS bulk process using multifunctional initiators with varying functionality and structure: DEKTP (cyclic trifunctional), PDP (cyclic bifunctional) and L331 (linear bifunctional). The theoretical work consisted of the development of a comprehensive, generic yet detailed mathematical model for bulk HIPS polymerization using multifunctional initiators. The model predicts the evolution of the main polymerization variables (including conversion, molecular weights, grafting efficiency) as well as the detailed molecular structure of the polymeric species (free polystyrene, residual polybutadiene and graft copolymer), and the melt flow index of the obtained HIPS. The model was adjusted and validated using experimental results, obtaining a good agreement between measured and predicted values. The model was used to theoretically evaluate the effect of the operating conditions on the molecular and physical characteristics of the obtained polymer. It was found that the use of multifunctional initiators leads to high polymerization rates and high molecular weights simultaneously, while promoting the grafting of styrene onto butadiene, generating a microstructure with salami‐type morphologies. POLYM. ENG. SCI., 58:198–212, 2018. © 2017 Society of Plastics Engineers